Workshop on Re-designing Interactive and Engaging Digital Learning for Elementary School Teachers with the Wheel of Names and Wordwall Platforms - Yuliyanto, Aan; Suri, Sofyan; Destiani, Kania Dwi; Trissa, Trissa; Utami, Tri Lita; Komar, Komar; Wulansari, Yuli Sri; Nurlela, Ela; Fitriani, Syifa; Prasetya, Hanjas; Juwendi, Juwendi (Politeknik Negeri Samarinda, 2024)
Implementing learning in the digital era requires teachers to continue to innovate in looking for interesting learning alternatives. Some digital platforms that can be used are Wheel of Names and Wordwall. The workshop on using the Wheel of Names and Wordwall platforms was held by students from the Pangeran Dharma Kusuma Institute through service activities, namely Community Service Program in Pondoh Village, Juntinyuat, Indramayu. This activity collaborates with Elementary School Teacher Education Lecturers who have expertise in digital literacy and digital learning. The first stage of activities was carried out in coordination with the school. The implementation stage is training in using the Wheel of Names and Wordwall platforms through a workshop with the theme Design Interactive and Exciting Digital Learning Activities. Participants as many as 10 elementary school teachers were allowed to listen and practice directly with resource persons regarding the implementation of digital learning, especially using the Wheel of Names and Wordwall platforms Evaluation of this activity is by using a questionnaire with the help of Google Form after the workshop is held. 87.5% of teachers were satisfied with the digital learning workshop and felt it helped design digital learning evaluations and was very innovative so they were encouraged to try it. However, 37.5% of teachers still find it difficult to practice digital platforms. Thus, through a series of digital learning workshop activities, it is hoped that educators can implement digital learning easily and effectively